The Effects Of Ship Loading Cost (General Cargo), Unit Ship’s Call And Ship’s Gross Tonnage Towards Non-Migas (Oil And Gas) Exports, With Four Destination Countries To U.S.A, Japan, Australia, And United Kingdom At Port Of Surabaya, Indonesia In 2014-2016 - Sembiring, Murpin Josua; Sasono, Herman Budi (Archives of Business Research, 2018)
The importance of international trade in the development of Indonesia economy which will increase the export role especially in non-oil and gas export. However, the export activities have to be supported by the availability of ships since the shipping facilities having a very important role in the sea transport system. This research was conducted with the aim to analyze the influence of Ship Loading Costral Cargo), Unit ship call, and Ship’s Gross Tonnage on Non-Oil and Gas Export Destination Countries to U.S.A, Japan, Australian, and U.K at Port of Surabaya Indonesia Year 2014 – 2016. This research used quantitative approach, with secondary data engineering as data collection. The data analysis techniques which used is SEM analysis using PLS. The results in this paper reveals that (1) Ship Loading Cost (General Cargo) has a significant influence on Non-Oil and Gas Exports, (2) Unit Ship Call has no significant influence on Non-Migas (Oil and Gas) Exports (3) Gross Tonnage is insignificant to Non Oil and Gas Exports.